Unemployment in the European Union: institutions, prices, and growth - Marika Karanassou; Héctor Sala; Dennis J. Snower (Queen Mary University of London, Department of Economics, 2003)
This paper presents a reappraisal of unemployment movements in the European Union. Our analysis is based on the chain reaction theory of unemployment, which focuses on (a) the interaction among labor markets adjustment processes, (b) the interplay between these adjustment processes and the dynamic structure of labor market shocks, and (c) the interaction between the adjustment processes and economic growth. We divide the shocks into institutional variables, price variables, and growth drivers. Estimating a system of labor market equations for a panel of EU countries, we derive the dynamic unemployment responses to each shock. Our analysis permits us to distinguish between the short- and long-run effects of the shocks. Different shocks generate different degrees of "unemployment persistence" (responses to temporary shocks) and "unemployment responsiveness" (responses to permanent shocks). We find that the growth drivers play a dominant role in accounting for the main swings in EU unemployment.
Keywords: J64; J60; J32; E37; E30; 330; Unempolyment; natural rate; labor market shocks; chain reaction theory; employment; labor force participation; wage determination; Arbeitslosigkeit; Hysteresis; Schock; Arbeitsmarktflexibilisierung; Internationaler Wettbewerb; Konjunktur; Schätzung; EU-Staaten